Analysis of the Influence of Product Cost and Perceived Advertising Costs Through Digital Devices on Digital Brand Equity of American Fast-Food Products McDonalds - Sudirjo, Frans; Fajri, Muhammad Iqbal; Ilyas, Arifai; Kespandiar, Tengku; Permadi, Indra (Jurnal Informasi dan Teknologi, 2024)
The purpose of this research is to demonstrate and examine how perceived advertising budget and pricing deals affect perceived quality and brand image, as well as how brand loyalty, brand awareness, and brand image are affected. Descriptive research is what this study is doing. The research approach employed by the investigators was a cross-sectional design. In this study, a questionnaire is used to collect data. This study's target demographic consists of all individuals who have visited, seen, and bought merchandise. Scientists employed judgmental sampling, a non-probability sampling method. One hundred persons made up the research sample. This study makes use of the confirmatory factor analysis approach in conjunction with the SEM data processing technology. The analysis's findings indicated that perceived advertising spending positively impacted perceived quality. Brand loyalty is positively impacted by perceived ad spend. Brand recognition is positively impacted by perceived ad spending. Brand image benefits from perceived advertising expenditure. Discounts on prices positively impact the perception of quality. Discounts have a detrimental effect on a brand's reputation. Thus, these results provide important insights for companies in designing their marketing strategies. They need to carefully consider the allocation of their promotional funds, ensuring that investment in perceived advertising spending is balanced with the benefits derived while also being mindful of the risks associated with excessive use of price deals. By understanding the relationship between these factors, companies can optimize their marketing efforts to strengthen their brand image and improve their product performance in the marketplace.